Wealth of experience : - Clarke, Andrew S. (John Wiley & Sons, 2003)
There are many paths to investment success, but few are as straight and true as Vanguard’s. Simplicity, thrift, and broad diversification are powerful allies. Andy Clarke has assembled a wealth of real-world examples that will show you how to get these forces working in your favor.